Autosomal recessive cutis laxa Type II: Report of novel mutation in a child - Rakesh Kumar; Sheetal Sharda; Vimlesh Soni; Kaniyappan Nambiyar (Wolters Kluwer Medknow Publications, 2017)
Autosomal recessive cutis laxa type-II (ARCLII) is a spectrum of clinical disorders with prenatal and postnatal growth retardation, cutis laxa, dysmorphism, and skeletal abnormalities. We report the case of a 14-month-old boy with developmental delay, hypotonia, dysmorphism, and loose skin. A novel homozygous variant was observed in ATP6VOA2 gene. Clinical spectrum of ARCLII is highly heterogeneous and molecular analysis should be done to confirm the diagnosis.